Copper for the Pharaoh: identifying multiple metal sources for Ramesses' workshops from bronze and crucible remains - Rademakers, Frederik; Rehren, Thilo; Pernicka, Ernst (Journal of archaeological science, 2017)
The origin of copper used in Late Bronze Age (LBA) Egypt is very poorly understood despite its cultural and economic importance attested in archaeological and historical sources. Extensive literature discusses major LBA copper sources such as Cyprus (oxhide ingots), Oman (bun ingots) and Egyptian-controlled sites in the Sinai. This paper presents new chemical and lead isotope data for Egyptian copper alloys excavated in several bronze production workshops from the New Kingdom capital Pi-Ramesse, expanding on earlier data from Amarna. Supporting data is obtained from the analysis of crucible remains from the same context, for which the potential contribution of lead isotope analysis is critically evaluated. Diachronic changes in the provisioning of these Egyptian workshops are discussed, incorporating an extensive overview of currently known Egyptian mining and metallurgy. The results have major implications for our understanding of LBA copper circulation in the wider region, for the first time analysing a major Egyptian ‘consumer’ assemblage. The analytical results reveal a complex picture of variable copper supply to the Ramesside workshops, which involved both the recycling of existing bronzes and the use of freshly smelted copper from various origins to produce fresh alloys. Importantly, this includes crucial new evidence for the melting of (Cypriot) oxhide ingot fragments in crucibles for alloying. The royal, internationally connected nature of these workshops makes Pi-Ramesse an exceptional case study of LBA metal trade, and hypotheses raised in this paper highlight the need for more extensive analysis of ancient Egyptian copper artefacts to grasp metal circulation throughout Egypt's long history. More refined frameworks, incorporating the variety of private as well as royal contexts, will improve understanding of Egypt's ancient economic organisation. This paper offers new perspectives onto LBA metal supply and consumption networks, with broader archaeological interpretative models of economic and political interactions across the wider ancient Near East.